Magnitude of Morning Surge in Blood Pressure Is Associated with Sympathetic but Not Cardiac Baroreflex Sensitivity - Johnson, Aaron W.; Hissen, Sarah L.; Macefield, Vaughan G.; Brown, Rachael; Taylor, Chloe E. (Frontiers in Neuroscience, 2016)
The ability of the arterial baroreflex to regulate blood pressure may influence the magnitude of the morning surge in blood pressure. The aim was to investigate the relationships between sympathetic and cardiac baroreflex sensitivity (BRS) and the morning surge. Twenty-four hour ambulatory blood pressure was recorded in 14 young individuals. The morning surge was defined via the pre-awakening method, which is calculated as the difference between mean blood pressure values two hours before and two hours after rising from sleep. The mean systolic morning surge, diastolic morning surge and morning surge in mean arterial pressures were 15 ± 2 mmHg, 13 ± 1 mmHg and 11 ± 1 mmHg respectively. During the laboratory protocol, continuous measurements of blood pressure, heart rate and muscle sympathetic nerve activity (MSNA) were made over a 10-min period of rest. Sympathetic BRS was quantified by plotting MSNA burst incidence against diastolic pressure (sympathetic BRSinc), and by plotting total MSNA against diastolic pressure (sympathetic BRStotal). Cardiac BRS was quantified using the sequence method. The mean values for sympathetic BRSinc, sympathetic BRStotal and cardiac BRS were -1.26 ± 0.26 bursts/100hb/mmHg, -1.60 ± 0.37 AU/beat/mmHg and 13.1 ± 1.5 ms/mmHg respectively. Significant relationships were identified between sympathetic BRSinc and the diastolic morning surge (r =0.62, p =0.02) and the morning surge in mean arterial pressure (r =0.57, p =0.03). Low sympathetic BRS was associated with a larger morning surge in mean arterial and diastolic blood pressure. Trends for relationships were identified between sympathetic BRStotal and the diastolic morning surge (r =0.52, p =0.066) and the morning surge in mean arterial pressure (r =0.48, p =0.095) but these did not reach significance. There were no significant relationships between cardiac BRS and the morning surge. These findings indicate that the ability of the baroreflex to buffer increases in blood pressure via reflexive changes in MSNA may play a role in determining the magnitude of the morning surge in blood pressure.